Crystal structure of ziprasidone hydrochloride monohydrate, C21H22Cl2N4OS(H2O). Issue 3 (12th August 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of ziprasidone hydrochloride monohydrate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Ziprasidone hydrochloride monohydrate crystallizes in space group P -1 (#2) with a = 7.250 10(3), b = 10.986 66(8), c = 14.071 87(14) Å, α = 83.4310(4), β = 80.5931(6), γ = 87.1437(6)°, V = 1098.00(1) Å 3, and Z = 2. The ziprasidone conformation in the solid state is very close to the minimum energy conformation. The positively-charged nitrogen in the ziprasidone makes a strong hydrogen bond with the chloride anion. The water molecule makes two weaker bonds to the chloride, and acts as an acceptor in an N–H⋯O hydrogen bond. The powder pattern is included in the Powder Diffraction File ™ as entry 00-064-1492.